Knowledge Level of Dental and Oral Health Related to Halitosis in Pregnant Women - Nurfianti; Ronal, Ahmad; Tiani, Sintia Aris; Surachmin, Audiawati (YARSI Dental Journal, 2023)
Background: A woman will generally experience a period of pregnancy, dental and oral health was important and needed to be considered, especially during pregnancy. Increased hormone levels that occurred during pregnancy can cause pregnant women to be susceptible to disorders of the oral cavity such as halitosis. Efforts that can be made to overcome this was through knowledge that can be obtained from various sources. Islam emphasized the health of the mother during pregnancy and the fetus in her womb. Objective: To determine the level of knowledge of oral health related to halitosis in pregnant women and its review from an Islamic perspective. Methods: The research design was cross sectional. The sampling method was purposive sampling with a total sample of 105 pregnant women at the Setu 1 Health Center and Lemah Abang Health Center. Data were collected through a questionnaire and the data were analyzed using the Chi-Square test. Results: The results of the Chi-Square test on the level of knowledge of oral health related to halitosis in pregnant women based on the respondent's age, gestational age, and last education showed that there was no statistically significant difference (p>0.05). Conclusion: Most of the pregnant women at the Setu 1 Public Health Center and Lemah Abang Health Center had a moderate level of knowledge about dental and oral health related to halitosis in pregnant women. Having good knowledge of oral health during pregnancy was the implementation of maqashid syariah in maintaining the soul of pregnant women and protecting the fetus they contain   Keywords: Halitosis, knowledge, oral health, pregnancy